Packaging of intron-containing genes into retrovirus vectors by alphavirus vectors - Li, Ke-Jun (The National Academy of Sciences, 1998)
Efficient and controllable expression of a transgene usually requires the presence of intron sequences and much efforts have been made to produce retrovirus vectors that can transduce and integrate genes with introns. However, this has proven difficult because the viral RNA is spliced when it is synthesized in the nucleus of a producer cell. We describe a novel approach to avoid this problem. In our system the retroviral RNA is synthesized in the cytoplasm of the cell, not in the nucleus, in a reaction driven by the Semliki Forest virus (SFV) expression system. The approach was tested with a recombinant Moloney murine leukemia virus genome containing the chloramphenicol acetyltransferase (CAT) gene in association with an intron. This was inserted into a SFV transcription plasmid and the corresponding SFV vector RNA was transcribed in vitro. BHK-21 cells were then transfected with this vector RNA together with two additional SFV vectors that encode the Moloney murine leukemia virus packaging proteins. Retrovirus vectors containing intron-CAT sequences were produced at titers up to 1.3 × 10(6) infectious particles per ml during a 5-hr incubation period. The vectors faithfully transduced the intron-containing CAT gene into NIH 3T3 cells, where the intron-CAT RNA was subjected to efficient splicing and used for high level enzyme expression. Thus, the results show that intron containing genes can be efficiently packaged into retrovirus vectors by the SFV expression system.